(untitled) (Research, Society and Development, 2020)
This article aims to explore, through a qualitative bibliographic search, the benefits brought by the implementation of the Six Sigma methodology, which, in turn, aims to use effective and efficient techniques and tools to improve improvements in any type of process within of a company. The Six Sigma can be defined as a management strategy and highly disciplined quantitative and objective dramatically increase business profitability through improved quality of products and processes and the increased satisfaction of customers and consumers. With the implementation of the Six Sigma methodology the company can recognize, identify opportunities and problems associated with corporate strategy to help reduce costs, increase productivity and address issues to improve the efficiency of all areas, ie the entire process by which the product manufactured passes to the final stage.